2016
DOI: 10.1007/s13762-016-1040-1
|View full text |Cite
|
Sign up to set email alerts
|

Interactive effects of cadmium and copper on metal accumulation, oxidative stress, and mineral composition in Brassica napus

Abstract: Heavy metals' frequent occurrence and toxicity caused considerable concerns in assessing the interactive effects of metals on exposed plants. Therefore, a hydroponic study was conducted to assess the growth response and physio-chemical changes in Brassica napus plants under single and combined stress of two environmentally alarming metals (Cd and Cu). Results showed that 15-day metal exposure to different metal concentrations (0, 50, 200 lM) significantly enhanced Cd accumulation, while lesser extent of Cu was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
21
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(26 citation statements)
references
References 56 publications
3
21
0
2
Order By: Relevance
“…However, excess concentration of these metals can affect the plant growth as we found in this study. Earlier, Mwamba et al [ 29 ] and Gill et al [ 14 ] found similar results of growth retardation in B. napus plants under Cu and Cr stress conditions, respectively. Here, we also studied the combined effect of Cu and Cr stress on the growth and physiology of B. napus plants and found that a combined application of Cu+Cr proved to be more toxic than Cr followed by Cu alone treatments in both cultivars.…”
Section: Discussionsupporting
confidence: 55%
“…However, excess concentration of these metals can affect the plant growth as we found in this study. Earlier, Mwamba et al [ 29 ] and Gill et al [ 14 ] found similar results of growth retardation in B. napus plants under Cu and Cr stress conditions, respectively. Here, we also studied the combined effect of Cu and Cr stress on the growth and physiology of B. napus plants and found that a combined application of Cu+Cr proved to be more toxic than Cr followed by Cu alone treatments in both cultivars.…”
Section: Discussionsupporting
confidence: 55%
“…Be-induced deleterious effects were also evident even at the lowest dose (100 μ M), except for shoot height and stem fresh weight in ZS 758, as well as root fresh weight in both ZS 758 and Zheda 622. In recent studies, we reported a differing level of metal tolerance ability of cultivars ZS 758 and Zheda 622 under Cr [ 6 ], Cu, and Cd [ 41 ] stress. However, in this study, a relatively less difference was observed in the sensitivity and tolerance ability of these cultivars against Be stress.…”
Section: Resultsmentioning
confidence: 99%
“…Metal phytotoxicity is considered to induce OS [45,46]. Scandalios [47] found that metals disturbed the normal balance between ROS and antioxidants in all aerobic cells, and a recently conducted study reported that increased antioxidant enzymatic activity has the capability of reducing OS for plants [45].…”
Section: Toxicity Of CD On Antioxidative Enzymatic Activitymentioning
confidence: 99%